Respostas

A melhor resposta!
2014-04-08T22:20:55-03:00
A)  (x+ \frac{1}{2} )^{2} = x^{2} +2.x. \frac{1}{2} + ( \frac{1}{2} )^{2} =x^{2} +x +  \frac{1}{4}

b) (x- 0,1 )^{2} =(x-  \frac{1}{10}  )^{2}= x^{2} -2.x. \frac{1}{10} + ( \frac{1}{10} )^{2} =x^{2} - \frac{1}{5} x +  \frac{1}{100}

c) (x+ 0,5 )^{2} =(x+  \frac{1}{2}  )^{2}= x^{2}+2.x. \frac{1}{2} + ( \frac{1}{2} )^{2} =x^{2} +  x +  \frac{1}{4}

d) (\frac{1}{3}-x )^{2} = ( \frac{1}{3} )^{2}-2.\frac{1}{3}.x + x^{2} = \frac{1}{9} - \frac{2}{3} x+ x^{2}
3 5 3